Appropriate flood control technology in a local trading area: Case study at Pulosari Kiosk Area in Malang City - Laksni Sedyowati; Nanang Mudjito; Gunawan Wibisono; Danes Satria Prayogo (Jurnal Penelitian, 2022)
To date, flood is a problem that often plagues the city of Malang. Floods that occur are mainly caused by poor drainage channels and silting of drainage channels due to people's habits of throwing garbage in rivers. In the Pulosari Kiosk Area of Malang city, the flood was worsened by the capacity of the Pulosari Channel which narrowed due to illegal building. In heavy rain, so much water overflowed into the Pulosari Road, resulting in losses to traders in the area. The purpose of this study was to find a solution to reduce flooding in the Pulosari Channel with the appropriate flood control technology in the area. This study used interviews and questionnaires to investigate the community's response to flood control development efforts. Data analysis was carried out using statistical analysis to obtain a description of the community response to a flood control system implemented by the city government. The research results show that constructing flood diversion channels in the upper area, and educating the community about flood risk management is the best solution in this area to minimize flood losses.